2002
DOI: 10.2166/wst.2002.0680
|View full text |Cite
|
Sign up to set email alerts
|

Non-point source pesticide removal by a mountainous wetland

Abstract: Non-point source (NPS) pollution is believed to be one of the major causes of impairment of water bodies. Among NPS pollution, agricultural NPS pollution is considered to be the largest single category resulting in water quality deterioration. Pesticides are some the most ubiquitous of these agricultural NPS pollutants. In this study, a mountainous wetland was selected to investigate the effects of the natural wetland system on the NPS pesticide (atrazine) removal to maintain the surface water quality. The sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Other pollutants and compounds can be mitigated by NFW sink processes (and/or transformation; see below). For example, microbial methanogenesis completely removed the pesticide atrazine from a mountainous bog in North Carolina (Kao et al 2002). The environmental contaminants cobalt (Co) and nickel (Ni) were remediated by wetland plants common in forested NFWs; plant concentrations were found to range from 1 to 530 mg Co/kg and up to 250 mg Ni/ kg (Brooks et al 1977).…”
Section: Chemicalmentioning
confidence: 99%
“…Other pollutants and compounds can be mitigated by NFW sink processes (and/or transformation; see below). For example, microbial methanogenesis completely removed the pesticide atrazine from a mountainous bog in North Carolina (Kao et al 2002). The environmental contaminants cobalt (Co) and nickel (Ni) were remediated by wetland plants common in forested NFWs; plant concentrations were found to range from 1 to 530 mg Co/kg and up to 250 mg Ni/ kg (Brooks et al 1977).…”
Section: Chemicalmentioning
confidence: 99%
“…Yet, it has to be noted that almost all available studies dealt with strongly sorbing insecticides (e.g., chlorpyrifos) with a strong tendency to adsorb to macrophytes, suspended particles or bed sediment. Some studies (Kadlec and Hey 1994;Seybold and Mersie 1999;Moore et al 2000;Kao et al 2002;Stearman et al 2003;Bouldin et al 2005) investigated the fate and transport of the moderately sorbing herbicide atrazine in constructed wetlands. Moore et al (2000) found that a travel distance of 100-280 m through the wetland would be necessary to achieve an effective runoff mitigation (more precisely: an atrazine concentration in outflow corresponding to the NOEC for higher aquatic plants).…”
Section: Constructed Wetlandsmentioning
confidence: 99%
“…chlorpyrifos) with a strong tendency to adsorb to macrophytes, suspended particles or bed sediment. Some studies (Kadlec and Hey, 1994;Seybold and Mersie, 1999;Moore et al, 2000;Kao et al, 2002;Stearman et al, 2003;Bouldin et al, 2005) investigated the fate and transport of the moderately sorbing herbicide atrazine in constructed wetlands. Moore et al (2000) found that a travel distance of 100-280 m through the wetland would be necessary to achieve an effective runoff mitigation (more precisely: an atrazine concentration in outflow corresponding to the NOEC for higher aquatic plants).…”
Section: Constructed Wetlandsmentioning
confidence: 99%